Fat‐Shaped Microbiota Affects Lipid Metabolism, Liver Steatosis, and Intestinal Homeostasis in Mice Fed a Low‐Protein Diet. Issue 15 (1st July 2020) - Busnelli, Marco; Manzini, Stefano; Jablaoui, Amin; Bruneau, Aurélia; Kriaa, Aïcha; Philippe, Catherine; Arnaboldi, Francesca; Colombo, Alice; Ferrari, Benedetta; Ambrogi, Federico; Maguin, Emmanuelle; Rhimi, Moez; et al.
Abstract : Scope: Protein malnutrition is characterized by stunted growth, hepatic steatosis and a damaged gut mucosal architecture. Since high‐fat shaped gut microbiota (HFM) has an increased ability in providing nutrients and energy from food to the host, the aim of this study is to determine whether such a microbiota could beneficially impact on the consequences of malnutrition. Methods and results: The cecal content of specific pathogen free C57Bl/6J mice fed a high‐fat diet or a low‐protein diet is transplanted in two groups of germ‐free C57Bl/6J recipient mice, which are subsequently fed a low‐protein diet for 8 weeks. Body weight gain is comparable between the two groups of microbiota‐recipient mice. The HFM led to a worsening of microvesicular steatosis and a decrease of plasma lipids compared to the low‐protein shaped microbiota. In the small intestine of mice receiving the HFM, although significant histological differences are not observed, the expression of antimicrobial genes promoting oxidative stress and immune response at the ileal epithelium (Duox2, Duoxa2, Saa1, Ang4, Defa5) is increased. Conclusion: The transplant of HFM in mice fed a low‐protein diet represents a noxious stimulus for the ileal mucosa and impairs hepatic lipoprotein secretion, favoring the occurrence of hepatic microvesicular steatosis. Abstract : Malnutrition contributes to more than 50% of the 10 million children deaths every year. In this study, the transplant of a microbiota obtained from donors eating a high‐fat diet does not ameliorate nutrient availability in mice fed a low‐protein diet, but it modulates plasma lipid levels, worsens liver steatosis, and alters the homeostasis of the intestinal mucosa.